Biallelic HFM1 variants cause non-obstructive azoospermia with meiotic arrest in humans by impairing crossover formation to varying degrees. Issue 7 (8th May 2022) - Xie, Xuefeng; Murtaza, Ghulam; Li, Yang; Zhou, Jianteng; Ye, Jingwei; Khan, Ranjha; Jiang, Long; Khan, Ihsan; Zubair, Muhammad; Yin, Hao; Jiang, Hanwei; Liu, Wei; et al.
Abstract: STUDY QUESTION: Do variants in helicase for meiosis 1 ( HFM1 ) account for male infertility in humans? SUMMARY ANSWER: Biallelic variants in HFM1 cause human male infertility owing to non-obstructive azoospermia (NOA) with impaired crossover formation and meiotic metaphase I (MMI) arrest. WHAT IS KNOWN ALREADY: HFM1 encodes an evolutionarily conserved DNA helicase that is essential for crossover formation and completion of meiosis. The null mutants of Hfm1 or its ortholog in multiple organisms displayed spermatogenic arrest at the MMI owing to deficiencies in synapsis and severe defects in crossover formation. Although HFM1 variants were found in infertile men with azoospermia or oligozoospermia, the causal relationship has not yet been established with functional evidence. STUDY DESIGN, SIZE, DURATION: A Pakistani family, having two infertile brothers born to consanguineous parents, and three unrelated Chinese men diagnosed with NOA were recruited for pathogenic variants screening. PARTICIPANTS/MATERIALS, SETTING, METHODS: All the patients were diagnosed with idiopathic NOA and, for the Chinese patients, meiotic defects were confirmed by histological analyses and/or immunofluorescence staining on testicular sections. Exome sequencing and subsequent bioinformatic analyses were performed to screen for candidate pathogenic variants. The pathogenicity of identified variants was assessed and studied in vivo in mice carrying the equivalent mutations. MAIN RESULTS AND THE ROLE OF CHANCE: Six variants (homozygous or compound heterozygous) in HFM1 were identified in the three Chinese patients with NOA and two brothers with NOA from the Pakistani family. Testicular histological analysis revealed that spermatogenesis is arrested at MMI in patients carrying the variants. Mice modeling the HFM1 variants identified in patients recapitulated the meiotic defects of patients, confirming the pathogenicity of the identified variants. These Hfm1 variants led to various reductions of HFM1 foci on chromosome axes and resulted in varying degrees of synapsis and crossover formation defects in the mutant male mice. In addition, Hfm1 mutant female mice displayed infertility or subfertility with oogenesis variously affected. LIMITATIONS, REASONS FOR CAUTION: A limitation of the current study is the small sample size. Owing to the unavailability of fresh testicular samples, the defects of synapsis and crossover formation could not be detected in spermatocytes of patients. Owing to the unavailability of antibodies, we could not quantify the impact of these variants on HFM1 protein levels. WIDER IMPLICATIONS OF THE FINDINGS: Our findings provide direct clinical and in vivo functional evidence that HFM1 variants cause male infertility in humans and also suggest that HFM1 may regulate meiotic crossover formation in a dose-dependent manner. Noticeably, our findings from mouse models showed that HFM1 variants could impair spermatogenesis and oogenesis with a varying degree of severity and might also be compatible with the production of a few spermatozoa in men and subfertility in women, extending the phenotypic spectrum of patients with HFM1 variants. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Natural Science Foundation of China (31890780, 32070850, 32061143006, 32000587 and 31900398) and the Fundamental Research Funds for the Central Universities (YD2070002007 and YD2070002012). The authors declare no potential conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.